Analyzing the Impact of Occupational Safety Programs on Work Productivity Using Fault Tree Analysis - Alex Christhoper; Dareen Dominic (Vertex, 2023)
This research delves into the intricate relationship between the implementation of an occupational safety program and its influence on work productivity within organizational settings. Employing fault tree analysis as a primary methodology, the study aims to scrutinize the efficacy of safety initiatives and delineate their direct correlation with productivity outcomes. Through a mixed-method approach integrating qualitative and quantitative analyses, the research examines the effectiveness of safety programs in mitigating workplace hazards and fostering a culture of safety. The fault tree analysis dissects causal factors, identifying critical pathways and root causes impacting work productivity. Findings reveal a symbiotic relationship between safety measures and productivity metrics. A well-executed safety program emerges as a catalyst for improved operational efficiency, employee engagement, and quality of work. The implications drawn from this study advocate for a paradigm shift, where safety initiatives are integrated strategically, nurturing an environment where safety and productivity coalesce seamlessly. This research contributes actionable insights for organizations to optimize safety measures, bolster productivity, and foster a culture where safety isn't just a priority but a fundamental value. Ultimately, the findings offer a compass guiding organizations towards a future where safety and productivity converge synergistically, shaping a landscape of sustained success and employee well-being.